Tunable Q-switched erbium-doped fiber laser in the C-band region using nanoparticles (TiO2) - Ahmad, Harith; Reduan, Siti Aisyah; Ruslan, Nur E'zzati; Lee, Cherrie Sue Jing; Zulkifli, Mohd Zamani; Thambiratnam, Kavintheran (Elsevier, 2019)
A tunable, passively Q-switched fiber laser using titanium dioxide (TiO2) as saturable absorber (SA) is proposed and demonstrated. The TiO2 SA has an insertion loss and modulation depth of 2.6 dB and 19.1 % respectively. The generated laser output has a repetition rate of 83.3 kHz and pulse-width of 0.08 μs at a maximum pump power of 270.0 mW. On the other hand, tuning the operational wavelength from 1534.0 nm to 1570 nm while fixing the pump power at 70.0 mW varies the repetition rate and pulse width from 50.5 to 22.2 kHz and 1.3 to 2.7 μs respectively. The results indicate that TiO2 could be an inexpensive and efficient SA for generating passively Q-switched fiber laser.